2020
DOI: 10.1038/s41598-020-65019-8
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Duration of the Pre-Operative Hospitalization is Associated with an Increased Risk of Healthcare-Associated Infections after Cardiac Surgery

Abstract: Nosocomial infections are a common complication in clinical practice with major impact on surgical success and patient outcome. The probability of nosocomial infections is rapidly increasing during hospitalization. Therefore, we investigated the impact of a prolonged pre-operative hospital stay on the development of post-operative infection. Within this prospective observational study, 200 patients scheduled for elective cardiac surgery were enrolled. Patients were followed during hospital admission and screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
6
0
3
Order By: Relevance
“…Various studies have found longer duration of stay in hospital and nosocomial infections among patients. 13 , 14 The COVID-19 positivity among the patients admitted in the hospital for some non-COVID related etiology indicate nosocomial/hospital acquired infection as found in our current study. This is similar to the reports of acquiring COVID-19 infection among non-COVID patients from other hospitals settings where nosocomial infections have been reported.…”
Section: Discussionsupporting
confidence: 77%
“…Various studies have found longer duration of stay in hospital and nosocomial infections among patients. 13 , 14 The COVID-19 positivity among the patients admitted in the hospital for some non-COVID related etiology indicate nosocomial/hospital acquired infection as found in our current study. This is similar to the reports of acquiring COVID-19 infection among non-COVID patients from other hospitals settings where nosocomial infections have been reported.…”
Section: Discussionsupporting
confidence: 77%
“…However, it can be seen that the highest number of infections was observed in the first stay, where the largest number of patients were hospitalized but in the period of hospitalization over 181 days, when fewer patients were hospitalized the number of infections was the highest, which suggests that the duration of hospitalization increases the risk of developing NI. In studies conducted by Sulzgruber et al, it can also be noted that the frequency of nosocomial infections associated with postoperative care increased significantly with the length of the patient's pre-operative hospitalization [25].…”
Section: Discussionmentioning
confidence: 93%
“…Otros factores clínico-quirúrgicos presentaron una asociación significativa con el riesgo de infección temprana en el presente estudio, como el tiempo desde el ingreso hospitalario hasta el procedimiento quirúrgico, el cual ha sido identificado como un factor asociado a un mayor riesgo de infecciones de sitio operatorio en otros contextos [47][48][49][50] . Su asociación con este desenlace puede derivar de una mayor exposición a patógenos nosocomiales y a la depleción nutricional secundaria al ayuno prolongado en espera de la realización del procedimiento quirúrgico, entre otros 47 .…”
Section: Discussionunclassified